Ordering Power under the Party: A Relational Approach to Law and Politics in China. Issue 1 (14th May 2019) - WANG, Juan; LIU, Sida
Abstract: Existing scholarship of China's legal institutions has primarily focused on individual institutions, such as the court, the police, or the legal profession. This article proposes a relational approach to the study of political-legal institutions in China. To understand the order and exercise of power by various political-legal institutions, the relational approach emphasizes the spatial positions of actors or institutions (the police, courts, lawyers, etc.) within the broader political-legal system and their mutual interactions. We suggest that the changing ideas of the Chinese leadership about the role of law as an instrument of governance have shaped the relations between various legal and political institutions. The interactions of these political-legal institutions (e.g. the "iron triangle" of the police, the court and the procuracy) further reveal the dynamics of power relations at work.